2007
DOI: 10.1097/jom.0b013e318124a93f
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of Serum Lipids and Liver Enzymes in Workers With Occupational Exposure to Ammonium Perfluorooctanoate

Abstract: These medical surveillance data collected on workers for up to 25 years contributes useful information on the effects of ammonium perfluorooctanoate exposure on human liver and lipid chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
122
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(127 citation statements)
references
References 30 publications
4
122
1
Order By: Relevance
“…As shown in Supplementary Table S3, previous studies have investigated the associations between serum lipids and PFAAs concentrations (Emmett et al, 2006;Sakr et al, 2007a;Sakr et al, 2007b;Frisbee et al, 2010a;Nelson et al, 2010;Eriksen et al, 2013;Fisher et al, 2013). However, those data are not always consistent.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…As shown in Supplementary Table S3, previous studies have investigated the associations between serum lipids and PFAAs concentrations (Emmett et al, 2006;Sakr et al, 2007a;Sakr et al, 2007b;Frisbee et al, 2010a;Nelson et al, 2010;Eriksen et al, 2013;Fisher et al, 2013). However, those data are not always consistent.…”
Section: Discussionmentioning
confidence: 66%
“…One cross-sectional study carried out among occupational population with a much higher exposure level observed a modest but statistically significant, positive relationship between serum PFOA and TC, LDLC, for each increase in 1 ng/mL in serum PFOA, TC and LDLC increases by 0.10 Â 10 À 3 and 0.07 Â 10 À 3 mmol/L, respectively (Sakr et al, 2007a). In a longitudinal study, Sakr et al (2007b) found serum PFOA was positively associated with TC, with an increase of 0.03 Â 10 À 3 mmol/L of cholesterol for each 1 ng/mL increase in PFOA. Another longitudinal study investigated the association between within-individual changes in serum PFAAs and changes in serum lipid levels; they found that there was a tendency for people with greater declines in serum PFOA to have greater LDLC decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of Sprague-Dawley rats to PFOS and PFOA at a dose of 20 mg/kg resulted in hepatomegaly and severe histological changes of the liver, such as fatty degeneration, hepatocytic necrosis, and inflammatory cell infiltration 5) . Positive correlations of serum levels of PFOA with serum liver enzymes (γ -GTP, GOT or GPT) have been reported in several studies on fluorochemical workers with heavy exposure to PFOA or its related substance 32,33) but not in others 34,35) . Positive correlations were also observed between serum levels of PFOA or PFOS and hepatic enzymes (γ -GTP and/or GPT) in populations of the U.S. with high or background exposure to these PFCs 36,37) .…”
Section: Discussionmentioning
confidence: 99%
“…Some epidemiological studies have shown positive associations between PFOA and lipids in general human populations. For example, in occupationally exposed employees, increased PFOA was associated with increased total cholesterol and triglycerides Sakr et al 2007). Recently, a much larger study of adults from environmentally exposed and adjacent communities reported a positive association between PFOA and total and low-density lipoprotein cholesterol, and a less clear association of PFOA with triglycerides (Steenland et al 2009).…”
Section: Introductionmentioning
confidence: 99%